Connect, converse, collaborate: Encountering belonging and forging resilience through creative practice - Crews, Sarah; Allinson, Jodie (Journal of University Teaching and Learning Practice, 2022)
This paper is a dialogue between two colleagues who teach drama and performance in Higher Education. Our work here has developed across a series of formal, semi-structured and informal discussions about our experiences of teaching and supporting students within the Drama and Performance department at University of South Wales. Instantly we connected on our commitment to prioritising student needs and our intentions to co-construct reflexive learning spaces. Within the disciplines of drama and performance, we (Allinson and Crews) see practice, collaboration and dialogue as equally important and core to all learning environments and encounters. Because of this we continually question how to hold a space for students through focusing on individual needs and difference, whilst simultaneously attempting to find connection through shared intentions and practices. Acknowledging individual and collective anxiety in learning environments is important because, left unchecked, these individual anxieties risk generating collective frustration, resistance to the creative process and fatigue. Openly discussing and agreeing on how to create spaces and structures for feeling heard and seen fosters belonging and in turn resilience, both in ourselves and our students. Here we propose that working within creative practices and exploring dynamic ways of holding space for ourselves and for students generates repeated experiences of successful encounters that build resourcefulness and resilience. This allows educators and students to collectively and mindfully encounter future situations and engage with them transformatively.